FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA PEROKOK PASIF(Studi Kasus Pada Keluarga Perokok Aktif Di Desa Bukit Mulya Kecamatan Subah Kabupaten Sambas Kalimantan Barat) - Mustolih, Ahmad; Trisnawati, Elly; Ridha, Abduh (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2015)
Hypertension is one of the health problems of major concern in the health sector, because of morbidity and high mortality as well as the impact in the long term. Hypertension was almost total in all areas, especially urban areas, and lately there is a tendency of increase in the incidence of hypertension in rural areas many factors that can cause hypertension. One of them smoke. The nicotine contained in tobacco smoke stream side 4-5 times larger than rorkok mainstream smoke, it is most impact on secondhand smoke, especially in housewives are more exposed to cigarette smoke while her husband. The incidence of hypertension has increased in every him. In 2011 the proportion of incident hypertension of 7.89%, increasing to 8.2 in 2012 and 12.4 in 2013. This study aims to determine the factors associated with hypertension in passive smokers in the village of Bukit Mulya District of Sambas district Subah ,The design of this research study Cross Sectional.Sampel 117 people were taken by purposive sampling technique using chi-square test with a confidence level of 95%.The results showed that there is a significant number of cigarettes smoked husband (p value = 0.041, PR = 2.708, 95% CI = 1.128 to 6.509), the type of cigarettes smoked husband (p value = 0,027 PR = 3.947, 95% CI = 1.194 to 13.040), where smoking husband (p value = 0.041 PR = 2.860, 95% CI = 1.121 to 7.295), the number of smokers in the family (p value = 2,400 PR 0.47, 95% CI = 1.085 to 5.309) with hypertension in passive smokers (wife). Variables that are not related diseases namely long exposure (p value = 0.328).It is advised to always be warned not to smoke in the house and avoid exposure to cigarette smoke.Â Keywords: Hypertension, the number of stems, type, place, the number of smokers.